Road Traffic Crash Cost Human Capital Approach: A Case Study of Kailali District - Dhami, Maheshwari; Shrestha, Pradeep Kumar; Tiwari, Hemant (Journal on Transportation System and Engineering, 2025)
Road traffic crashes continue to impose substantial economic and social burdens, particularly in developing countries such as Nepal, where resources for road safety are limited. This study employs the Human Capital Approach to estimate the costs of road traffic crashes in Kailali District for the fiscal years 2022–23 and 2023–24. The costs associated with crashes were categorized into six main components: lost productivity, quality of life losses, medical expenses, property damage, damage-only crashes, and administrative costs. Using secondary data obtained from traffic police records, hospitals, insurance companies, and other relevant sources, the study found that the average age of fatality was 38 years in 2022–23 and 37 years in 2023–24. Between 2022–23 and 2023–24, the total economic cost of road crashes rose by 38.93%, reflecting a growing financial and social burden. Among the cost components, lost productivity remained the largest contributor, followed by quality of life losses. Although medical expenses, property damage, administrative costs, and damage-only crashes accounted for smaller proportions of the total cost, they showed a noticeable upward trend. These findings highlight the pressing need for comprehensive and effective road safety measures in Kailali District to mitigate both the human and economic impacts of traffic crashes.